THE IMPROVE SPEAKING ABILITY THROUGH EARLY CHILDHOOD EDUCATION 5-6 YEARS OLD THROUGH ROLE PLAY IN ANAK BANGSA KINDERGARTEN CIOMAS BOGOR - Triyaningsih, Triyaningsih (Universitas Muhammadiyah Metro, 2016)
Abstract: This study is attempled to investigate about how improve the speaking ability through Role Play in Anak Bangsa Kindergarten Ciomas Bogor. Hypothesis tested are : there is different between the beginning assessment and the end assessment This study is conducted in TK Anak Bangsa,Ciomas Bogor on March until May in the second semester 2009/2010. this study uses the Kemmis and Mc. Taggart model of action research which consist of the four stage, those are : a) planning, 2) action, 3) observation, 4) reflection . the process of collecting the data is using the techigue of interview, observation, and portofolio. the data is analysed qualitatively and quantitatively. The result of the research shoe that, the learning analysis in the first cycle to the second cycle indicated that, the learning analysis in the first cycle to the second cycle indicated that, significantly theres is increasing oof the speaking ability of student which sight out by the positive respon to speaking ability performen. the quantitave data of student outcome learning is score of speaking performance with rating scale. the student more done their speakin performence ability with higt result. The research result also concluded that 1) The Role Play can impove speaking ability for kindergarden student, 2) managing and organization the condusive class can improve the speaking ability for kindergarten student, 3) portofolio assessment system improve the speaking ability for kindergarten student, and the other result of this research is Role Play can improve the learning activity and the student outcome learning. Keyword: kindergarten, speaking ability, assessment